2010
DOI: 10.2174/1875692111008010007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in Telomere Maintenance, with Implications on Tissue Renewal Capacity and Chronic Disease Pathologies

Abstract: Premature loss of telomere repeats underlies the pathologies of inherited bone marrow failure syndromes. Over the past decade, researchers have mapped genetic lesions responsible for the accelerated loss of telomere repeats. Haploinsufficiencies in the catalytic core components of the telomere maintenance enzyme telomerase, as well as genetic defects in telomerase holoenzyme components responsible for enzyme stability, have been linked to hematopoietic failure pathologies. Frequencies of these disease-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 209 publications
(281 reference statements)
0
19
0
Order By: Relevance
“…Frequency = 0, allele found in a family described in the literature but not in the Exome Sequencing Project.RRL activity, HEK activity and VA13 activity, direct assay results from this study.Published activity, references given in the same order as the activity values.RRL processivity determined by the linear regression method, and HEK processivity determined by the >15 repeats method, all from this study.Disease: IPF, idiopathic pulmonary fibrosis; AML, acute myloid leukemia; AA, aplastic anemia; DC, dyskeratosis congenita. a These alleles were originally reported as disease-associated, but the disease association is now thought to be modest [discussed in (14)].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequency = 0, allele found in a family described in the literature but not in the Exome Sequencing Project.RRL activity, HEK activity and VA13 activity, direct assay results from this study.Published activity, references given in the same order as the activity values.RRL processivity determined by the linear regression method, and HEK processivity determined by the >15 repeats method, all from this study.Disease: IPF, idiopathic pulmonary fibrosis; AML, acute myloid leukemia; AA, aplastic anemia; DC, dyskeratosis congenita. a These alleles were originally reported as disease-associated, but the disease association is now thought to be modest [discussed in (14)].…”
Section: Resultsmentioning
confidence: 99%
“…The rare inherited disorder dyskeratosis congenita (characterized by defects in highly proliferative tissues such as skin and bone marrow) has been traced to insufficient telomerase activity due to mutations in the dyskerin protein subunit (8), the telomerase RNA (9) and TERT (10), or in telomere components such as TINF2 and RTEL1 (11–13). Recently, other diseases including idiopathic pulmonary fibrosis and aplastic anemia have been associated with telomerase deficiency (14). Telomerase deficiency also contributes to multiple forms of cancer, presumably because short telomeres lead to genome instability which contributes to oncogenesis (15–18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, rs398652 genetic variants have an obvious impact on TL and esophageal squamous cell carcinoma susceptibility in Chinese populations [14]. While evidence for the causal role of TL variation in some chronic diseases has accumulated [15], the link between SNPs involved in telomere biology and the risk of hypertension (HTN), CHD, and its risk factors, has not been extensively studied in Korean populations. In this study, we examined whether SNPs previously reported to be associated with TL in humans are related to the incidence of HTN/CHD and risk factors of CVD, in a Korean population.…”
Section: Introductionmentioning
confidence: 99%
“…75 Despite this finding, there does appear to be an association between ex vivo cell senescence and organismal lifespan, and studies of telomerase mutations in humans have revealed an association with diseases of aging in which tissue compartments require a high degree of cell self-renewal. 76 Similarly, short telomeres have been linked with some tissue-specific degenerative diseases, and telomere length is evaluated as a clinical parameter in determining therapeutic approaches. 77 Ablation of senescent cells in progeroid mice has been shown to delay or rescue the aging phenotype at the organismal level, implicating senescent cells in the pathogenesis of age-related disease in vivo.…”
Section: Adult Stem Cells and Diseases Of Agingmentioning
confidence: 99%